Treatment Bundle Improves Outcomes in the Management of Candidemia at Large Urban Academic Medical Center. (4th October 2017) - Cook, Gregory; Advani, Shreena; Rab, Saira; Kandiah, Sheetal; Patel, Manish; Wong, Jordan
Abstract: Background: A candidemia treatment bundle (CTB) may increase adherence to guideline recommended candidemia management and improve patient outcomes. The purpose of this study was to evaluate the impact of a best practice alert (BPA) and order-set on optimizing compliance with all CTB components and patient outcomes. Methods: A single center, pre-/post-intervention study was completed at Grady Health System from August 2015 to August 2017. Post-CTB intervention began August 2016. The CTB included a BPA that fires for blood cultures positive for any Candida species to treatment clinicians upon opening the patient's electronic health record. The BPA included a linked order-set based on treatment recommendations including: infectious diseases (ID) and ophthalmology consultation, repeat blood cultures, empiric echinocandin therapy, early source control, antifungal de-escalation, intravenous to oral (IV to PO) switch, and duration of therapy. The primary outcome of the study was total adherence to the CTB. The secondary outcomes include adherence with the individual components of the CTB, 30-day mortality, and infection-related length of stay (LOS). Results: Forty-five patients in the pre-group and 24 patients in the CTB group with candidemia were identified. Twenty-seven patients in the pre-group and 19 patients in the CTB group met inclusion criteria. Total adherence with the CTB occurred in one patient in the pre-group and threepatients in the CTB group (4% vs. 16%, P = 0.29). ID was consulted in 15 patients in the pre-group and 17 patients in the CTB group (56% vs. 89%, P = 0.02). Source control occurred in three and 11 patients, respectively (11% vs. 58% P < 0.01). The bundle components of empiric echinocandin use (81% vs. 100%, P = 0.07), ophthalmology consultation (81% vs. 95%, P = 0.37), and IV to PO switch (22% vs. 32%, P = 0.5) also improved in the CTB group. Repeat cultures and antifungal de-escalation were similar among groups. Thirty-day mortality decreased in the CTB group by 10% (26% vs. 16%, P = 0.48). Median iLOS decreased from 30 days in the pre-group to 17 days in the CTB group ( P =  0.05). Conclusion: The CTB, with a BPA and linked order-set, improved guideline recommended management of candidemia specifically increasing the rates of ID consultation and early source control. There were quantitative improvements in mortality and iLOS. Disclosures: All authors: No reported disclosures.